Teaching Sociology Students to Become Qualitative-Researchers Using an Internship Model of Learner-Support - Tolich, Martin; Scarth, Bonnie; Shephard, Kerry (JSSE - Journal of Social Science Education, 2016)
This article examines the experiences of final year undergraduate sociology students enrolled in an internship course where they researched a local community project, mostly in small groups, for a client. A sociology lecturer supervised their projects. Course-related outcomes were assessed using conventional university procedures but a research process was used to evaluate the extent to which the cohort developed characteristics, or identities, of qualitative researchers. The research demonstrates that the students made many false starts but through processes of trial and error, and with effective support, they considered that they had increased their confidence and became capable of planning and carrying out research. For the students, this internship was not just another class. Their stories reflect on their abilities as researchers and adoption of attitudes towards appropriate research approaches, processes and outputs typical of professional qualitative researchers.